2024
DOI: 10.1037/mgr0000158
|View full text |Cite
|
Sign up to set email alerts
|

Doing the work: The role of inclusive leadership in promoting psychological safety and openness to diversity through diversity, equity, and inclusion practices.

Amanda Woods,
Stephanie A. Zajac,
Eric D. Middleton
et al.

Abstract: Strengthening diversity, equity, and inclusion (DEI) is paramount to effectively meet the needs of an increasingly diverse workforce. In health care, this is compounded with the need for providers to deliver patient-centered care that respects a diversity of backgrounds, values, and beliefs. In this article, we examine the effect of leader inclusiveness on team outcomes including psychological safety (PS) and openness to diversity in health care. Furthermore, we use social identity theory to examine team engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Leveraging social identity theory, Woods et al (2024) examined team engagement in diversity, equity, and inclusion (DEI) practices as a key mediator of the relationship between leader inclusiveness and team outcomes (psychological safety and openness to diversity) in a large U.S. health care institution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leveraging social identity theory, Woods et al (2024) examined team engagement in diversity, equity, and inclusion (DEI) practices as a key mediator of the relationship between leader inclusiveness and team outcomes (psychological safety and openness to diversity) in a large U.S. health care institution.…”
mentioning
confidence: 99%
“…Leveraging social identity theory, Woods et al (2024) examined team engagement in diversity, equity, and inclusion (DEI) practices as a key mediator of the relationship between leader inclusiveness and team outcomes (psychological safety and openness to diversity) in a large U.S. health care institution. Based on analysis of two surveys from 400 employees, the authors found that the relationship between employees’ perceptions of inclusive leadership was associated with greater psychological safety and greater openness to diversity among team members and that this relationship was mediated by team engagement in DEI practices.…”
mentioning
confidence: 99%